2015
DOI: 10.1016/j.tjog.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial carcinoma arising from an ovarian mature cystic teratoma

Abstract: The final pathology confirmed concomitant malignant transformation of urothelial carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 6 publications
0
16
0
1
Order By: Relevance
“…Due to the different components of a teratoma, there can be various malignant transformations, such as squamous cell carcinomas (75%-80%), adenocarcinomas (7%), sarcomas (7%), basal cell carcinomas, sebaceous gland carcinomas, malignant melanomas, small cell lung cancers, transitional cell carcinomas, clear cell carcinomas, and gliomas [1,[3][4][5][6] . The patholog-ical diagnosis confirmed that this case was a teratoma accompanied by the malignant transformation of a sebaceous gland carcinoma, which is very rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the different components of a teratoma, there can be various malignant transformations, such as squamous cell carcinomas (75%-80%), adenocarcinomas (7%), sarcomas (7%), basal cell carcinomas, sebaceous gland carcinomas, malignant melanomas, small cell lung cancers, transitional cell carcinomas, clear cell carcinomas, and gliomas [1,[3][4][5][6] . The patholog-ical diagnosis confirmed that this case was a teratoma accompanied by the malignant transformation of a sebaceous gland carcinoma, which is very rare.…”
Section: Discussionmentioning
confidence: 99%
“…An enhanced CT and MRI show higher resolution of the soft tissue and higher sensitivity to fat composition and calcification, but it is still difficult to predict the malignant transformation of a teratoma by CT and MRI scanning because of its complex tissue composition. When an enhanced CT or MRI shows a tumor diameter of ≥ 10 cm, cystic wall thickening, an unclear boundary, irregular lobulation, uneven solid component enhancement, transmural necrosis, surrounding tissue adhesion, and lymph node enlargement in the peritoneum, these symptoms indicate the possibility of invasive disease [5,11,12] . When compared with the traditional T1-weighted images, the fat-suppressed T1-weighted images show more clearly the contrast-enhanced solid part of the teratoma, which is helpful to predict the teratoma malignancy [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Mature cystic teratoma (MCT) is a common benign adnexal tumour in females in the reproductive age group. 1,2 Malignant transformation in mature cystic teratoma of the ovary is rare, occurring in only 1-2% of cases. 1,2 The most common malignancy is squamous cell carcinoma, which consists of about 80% of malignant transformations.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Malignant transformation in mature cystic teratoma of the ovary is rare, occurring in only 1-2% of cases. 1,2 The most common malignancy is squamous cell carcinoma, which consists of about 80% of malignant transformations. 1 Urothelial carcinoma in mature cystic teratoma is very rare and occurs in 1-2% of cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation